New and old predictive factors for breech presentation: our experience in 14 433 singleton pregnancies and a literature review. (14th June 2013) - Fruscalzo, Arrigo; Londero, Ambrogio P.; Salvador, Stefania; Bertozzi, Serena; Biasioli, Anna; Della Martina, Monica; Driul, Lorenza; Marchesoni, Diego
Abstract: Objective : Breech presentation represents a common indication for primary cesarean section in women presenting for parturition. This study aims to investigate the presence of new and old risk factors for breech presentation and to provide a literature review. Method: In this population-based retrospective cohort study, we collected data from 14 433 consecutive singleton deliveries occurred in a 3rd level hospital setting of northeast Italy between January 2001 and July 2009. Related risk factors and trends in breech presentation prevalence were also considered. Results: Mean maternal age was 31.78 years (±5.17) and mean gestational age at delivery 38.67 weeks (±2.54). Breech presentation prevalence in nullipara and pluripara was respectively 5.36% (415/7743) and 3.53% (236/6689; p < 0.05), and was significantly lower among Sub-Saharan-African women 2.62% (14/535) versus 4.51% (651/14432; p  < 0.05). Also advanced maternal age, early gestational age at delivery, neonatal female gender and low weight at delivery resulted associated with a higher prevalence of breech presentation. By multivariate logistic regression, the breech presentation resulted independently predicted by maternal age, ethnicity, parity, gestational age and neonatal weight MoMs at delivery, and neonatal gender. Conclusions : Advanced maternal age, early gestational age, low neonatal weight MoMs at delivery and female gender resulted to be risk factors for fetal breech presentation at delivery, while multiparity and Sub-Saharan-African ethnicity resulted to be protective.